Variants in the host genome may inhibit tumour growth in devil facial tumours: evidence from genome-wide association - Belinda Wright (Scientific Reports, 2017)
Abstract Devil facial tumour disease (DFTD) has decimated wild populations of Tasmanian devils (Sarcophilus harrisii) due to its ability to avoid immune detection and pass from host to host by biting. A small number of devils have been observed to spontaneously recover from the disease which is otherwise fatal. We have sequenced the genomes of these rare cases and compared them to the genomes of devils who succumbed to the disease. Genome-wide association, based on this limited sampling, highlighted two key genomic regions potentially associated with ability to survive DFTD. Following targeted genotyping in additional samples, both of these loci remain significantly different between cases and controls, with the PAX3 locus retaining significance at the 0.001 level, though genome-wide significance was not achieved. We propose that PAX3 may be involved in a regulatory pathway that influences the slowing of tumour growth and may allow more time for an immune response to be mounted in animals with regressed tumours. This provides an intriguing hypothesis for further research and could provide a novel route of treatment for this devastating disease.